The dark monk : a hangman's daughter tale - Pötzsch, Oliver (Pötzsch, Oliver. Hangman's daughter tale., 2012)
1660: Winter has settled thick over a sleepy village in the Bavarian Alps, ensuring every farmer and servant is indoors on the night a parish priest discovers he<U+2019>s been poisoned. As numbness creeps up his body, he summons the last of his strength to scratch a cryptic sign in the frost. Following a trail of riddles, hangman Jakob Kuisl, his headstrong daughter, Magdalena, and the town physician<U+2019>s son team up with the priest<U+2019>s aristocratic sister to investigate. What they uncover will lead them back to the Crusades, unlocking a troubled history of internal church politics and sending them on a chase for a treasure of the Knights Templar. But they<U+2019>re not the only ones after the legendary fortune. A team of dangerous and mysterious monks is always close behind, tracking their every move, speaking Latin in the shadows, giving off a strange, intoxicating scent. And to throw the hangman off their trail, they have ensured he is tasked with capturing a band of thieves roving the countryside attacking solitary travelers and spreading panic.